Integration of IR-UWB Services into Single- and Multi-Channel Optical Coherent OFDM Network - Kadum, Jaffar Emad; Fyath, Raad Sami (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
Distribution of wireless communication signals over implemented optical networks is a challenged task since the presence of wireless services may affect the performance of the existing wired ones. This paper addresses the possibility of integrating impulse radio-ultrawideband (IR-UWB) wireless services into implemented coherent optical orthogonal frequency division multiplexing (CO-OFDM) network. Simulation results are presented for the transmission of a 625Mb/s UWB signal with either 50Gb/s single-channel or three-channel OFDM system. Both Gaussian monocycle and 5th-order derivative Gaussian pulses are used to implement the UWB system with two modulation formats, namely ON-OFF keying (OOK) and biphase modulation (BPM). The simulation results reveal that the performance of the CO-OFDM channels is not affected in the presence of UWB signals.